DAMPAK FRAMING PEMBERITAAN KEBIJAKAN PELARANGAN MUDIK DI TIRTO.ID TERHADAP KEPERCAYAAN MASYARAKAT KEPADA PEMERINTAH - kalya nabila zuhdi (Jurnal Ilmu Komunikasi Acta Diurna, 2021)
This study aims to see the impact of the framing of the homecoming prohibition policy on public trust in the government considering that this topic is in accordance with the current situation (according to the context of the era). This study uses the Robert N. Entman model by paying attention to the Define Problems scheme, Diagnose Causes, Make Moral Judgment, and Treatment Recommendations. The results of this study indicate that the presentation of information through infographic media can provide a more interesting experience as well as can understand information easily because this infographic media contains the essence of the information itself. This shows that tirto.id has been able to provide objective information based on a number of factual things such as policies, field situations, and statements from experts. The impact is that the government is not consistent in implementing a policy, making people's trust in the government decrease, due to facts on the ground which show that there are still differences in treatment of someone in implementing a policy. This is shown in several warganet comments on the tirto.id Instagram account.